Sticky cost behavior in selling, general, and administrative costs in Indonesian manufacturing companies - Lusiana Lusiana; Ika Kristianti (University of Merdeka Malang, 2020)
Cost response to decreasing activity is often smaller compared to rising costs when there is an increase in activity volume. The phenomenon of the cost response is often referred to as sticky cost behavior. This study aimed to determine whether there was sticky cost behavior in selling, general, and administrative (SGA) costs of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The observation period was in 2015-2017. The sample used was 258 manufacturing companies selected by using a purposive sampling technique. The type of data used was panel data using quantitative methods in the form of stationary with panel data regression tests with the Generalized Least Square (GLS) model. We found that there was no sticky cost behavior in the SGA costs of manufacturing companies in Indonesia. This study implies that decision making on a scale of activity in a company is difficult to predict. JEL Classification: C33, G30, J39 How to Cite:Lusiana, Kristianti, I. (2020). Sticky cost behavior in selling, general, and administrative costs in Indonesian manufacturing companies. Jurnal Keuangan dan Perbankan, 24(2), 214-224.DOI: https://doi.org/10.26905/jkdp.v24i2.3195